Model Proposal for Evaluation of Technology Development Process: Conceptualisation and Scale Development - Fethi Aslan (Istanbul Business Research)
Traditional approaches based on intuitive decisions of executivies, teams, or individuals often prove inadequate in managing complex technology development processes. Theoretical models proposed for successful technology development processes emphasize the necessity of standardized processes. However, empirical evidence regarding the applications and results of these models is limited. In this context, a model has been developed to examine how standardized technology development processes are implemented at the organizational level in companies. This model is defined by a scale that includes dimensions of technical research, business research, development, and performance. The proposed model is based on data obtained from companies with the highest R&D expenditure in Turkey. The findings provide evidence that a structured technology development process at the corporate level is necessary for success. It has been revealed that technical and business research phases are particularly determining factors in the development process. Additionally, it has been determined that the correct implementation of these processes has a positive impact on the performance of the process.